(untitled) (Comparative & International Education Series, 2021)
This chapter focuses on the costs of higher education abroad and strategies of international students to cover these expenses. Evidence in this chapter comes from 20 qualitative semi-structured interviews with international students from Latvia who pursued higher education degrees in the USA, Great Britain, the Netherlands, Germany, France, Poland, and Sweden. Data reveals that international students pursue higher education abroad managing various sources of funding. Most students combine funding from several sources at once which include scholarships, family resources, loans and personal earnings. This is the case in countries with high tertiary education costs such as the USA and Great Britain as well as in countries with modest higher education costs for students such as Germany and Poland. Data also shows that the socioeconomic background of students directly influences strategies that international students use to generate funds for accessing higher education.